2008
DOI: 10.1073/pnas.0801728105
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pathways influence temporal niche

Abstract: In mammals, light input from the retina entrains central circadian oscillators located in the suprachiasmatic nuclei (SCN). The phase of circadian activity rhythms with respect to the external light:dark cycle is reversed in diurnal and nocturnal species, although the phase of SCN rhythms relative to the light cycle remains unchanged. Neural mechanisms downstream from the SCN are therefore believed to determine diurnality or nocturnality. Here, we report a switch from nocturnal to diurnal entrainment of circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…This response is surprising because dark pulses do not induce wheel running activity (24). We further show that there was no overall effect in animals lacking ipRGCs (i.e., aDTA).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This response is surprising because dark pulses do not induce wheel running activity (24). We further show that there was no overall effect in animals lacking ipRGCs (i.e., aDTA).…”
Section: Discussionmentioning
confidence: 59%
“…Using wheel-running activity, it has been shown that WT mice do not significantly increase activity during a dark pulse presented during the daytime (24). However, EEG/EMG recording is a direct measure of sleep state and therefore a more accurate representation of behavioral changes.…”
Section: Acute Dark Exposure Induces Wakefulness and Requires Rod-conmentioning
confidence: 99%
“…In mammals, a given animal can stably and predictably switch back and forth between different patterns in context-dependent ways (Kas and Edgar 1999;Mrosovsky 2003). The choice of a temporal niche takes place downstream of the suprachiasmatic nucleus (SCN) clock and is strongly influenced by light inputs (Mrosovsky and Hattar 2005;Doyle et al 2008). A comparable plasticity is observed in flies.…”
Section: Network Architecture Under Ld Cyclesmentioning
confidence: 98%
“…This suggests that the phase difference in the activity of nocturnal and diurnal animals is not caused by differences in the circadian clock but rather by how the clock couples to output mechanisms (3). In this issue of PNAS, Doyle et al (4) present a possible mechanism for how retinal mutations could also lead to a switch between nocturnal and diurnal behavior.…”
mentioning
confidence: 99%
“…In this issue of PNAS, Doyle et al (4) used the Per2 luciferase reporter line to show that the molecular clock is phased oppositely in doubleknockout and wild-type animals. In addition, the rhythms in peripheral tissues are also reversed.…”
mentioning
confidence: 99%